PENGEMBANGAN MEDIA DIORAMA UNTUK PEMBELAJARAN IPS KELAS IV SEKOLAH DASAR - Nurul Sapitri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to develop diorama learning media in social learning for grade IV elementary schools and to determine the feasibility of diorama media. This research used research and development (R&D) methods using the model 4D (Define, Design, Develop, Disseminate). This development produced a product that has been adapted to the basic competencies used, namely identifying economic activities and their relationship to the field of work. Data were collected through questionnaires and trials. The feasibility of diorama learning media was obtained from the validation results and students’ and teachers’ responses. The validation was carried out by media experts and material experts. The trial conducted was limited to 23 grade IV elementary school students. The trial results by material experts were in the very feasible category, and the validation by media experts was in the very feasible category. Similarly, the validation from media experts obtained a very feasible category. The results of this research showed that the diorama media was very feasible for social studies learning at grade IV elementary schools.